2008
DOI: 10.1097/pcc.0b013e3181668b33
|View full text |Cite
|
Sign up to set email alerts
|

Prospective detection of hyperglycemia in critically ill children using continuous glucose monitoring*

Abstract: Significant hyperglycemia is present in pediatric intensive care patients and may be underestimated by intermittent laboratory monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Egy osztályunkon ápolt, congenitalis centrális hypoventilatióban szenvedő újszülöttnél alkalmazott CGM rendkívül érzékenynek bizonyult a hyperinsulinaemia okozta hypoglykaemiák felderítésében [37]. Allen és mtsai 20, intenzív ellátásra szoruló gyermek betegben igazolták a CGM hasznosságát a hyperglykaemiák pontosabb felderítésében [38]. Joggal merülhet fel a kérdés, hogy a szubkután szövet-ben történő mérés mennyire megbízható olyan betegek esetében, akiknek kritikus állapota befolyással lehet a szöveti perfúzióra.…”
Section: Cgm Az Intenzív Osztályonunclassified
“…Egy osztályunkon ápolt, congenitalis centrális hypoventilatióban szenvedő újszülöttnél alkalmazott CGM rendkívül érzékenynek bizonyult a hyperinsulinaemia okozta hypoglykaemiák felderítésében [37]. Allen és mtsai 20, intenzív ellátásra szoruló gyermek betegben igazolták a CGM hasznosságát a hyperglykaemiák pontosabb felderítésében [38]. Joggal merülhet fel a kérdés, hogy a szubkután szövet-ben történő mérés mennyire megbízható olyan betegek esetében, akiknek kritikus állapota befolyással lehet a szöveti perfúzióra.…”
Section: Cgm Az Intenzív Osztályonunclassified
“…They have also been studied in small groups of children in the PICU and have shown that intermittent glucose measurement can miss significant episodes of hyperglycemia (20). Their role in routine measurement of glucose in the PICU is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The pinpoint of our study was not to ascertain the accuracy of current CGMS -we consider this question as being already solved by larger studies mentioned above [33][34][35][36][37][38][39][40][41] . We focused on glycaemia trends of operated patients, on identification of frequent patterns of glycaemic reaction to stress and on the determination of eventual CGM impact on glycaemic stability in individual cases.…”
Section: Hunger After the Surgerymentioning
confidence: 99%
“…Goldberg used them in a medical ICU in 2004 and found 98.7% of the paired values clinically acceptable; he evaluated CGM as a reducer of glycaemia fluctuations and a promising research tool 34 . Others found it useful for reducing hyperglycaemic episodes 35 . The analysis of two prospective randomized trials demonstrated clinically sufficient accuracy and safety 36,37 even in patients on vasopressors 38 .…”
Section: Introductionmentioning
confidence: 99%